病原真菌Candida glabrataの液胞膜 H+-ATPaseが酸化ストレス応答に及ぼす影響 - 西川, 博 (Oxford University Press, 2017)
Nagasaki University (長崎大学) 博士(医学) Vacuolar H+-ATPase (V-ATPase) is responsible for the acidification of eukaryotic intracellular compartments and plays an important role in oxidative stress response (OSR), but its molecular bases are largely unknown. Here, we investigated how V-ATPase is involved in the OSR by using a strain lacking VPH2, which encodes an assembly factor of V-ATPase, in the pathogenic fungus Candida glabrata. The loss of Vph2 resulted in increased H2O2 sensitivity and intracellular reactive oxygen species (ROS) level independently of mitochondrial functions. The Δvph2 mutant also displayed growth defects under alkaline conditions accompanied by the accumulation of intracellular ROS and these phenotypes were recovered in the presence of the ROS scavenger N-acetyl-l-cysteine. Both expression and activity levels of mitochondrial manganese superoxide dismutase (Sod2) and catalase (Cta1) were decreased in the Δvph2 mutant. Phenotypic analyses of strains lacking and overexpressing these genes revealed that Sod2 and Cta1 play a predominant role in endogenous and exogenous OSR, respectively. Furthermore, supplementation of copper and iron restored the expression of SOD2 specifically in the Δvph2 mutant, suggesting that the homeostasis of intracellular cupper and iron levels maintained by V-ATPase was important for the Sod2-mediated OSR. This report demonstrates novel roles of V-ATPase in the OSR in C. glabrata. 長崎大学学位論文 学位記番号:博(医歯薬)乙第50号 学位授与年月日:平成29年9月6日 Author: Hiroshi Nishikawa, Taiga Miyazaki, Hironobu Nakayama, Asuka Minematsu, Shunsuke Yamauchi, Kohei Yamashita, Takahiro Takazono, hintaro Shimamura, Shigeki Nakamura, Koichi Izumikawa, Katsunori Yanagihara, Shigeru Kohno, Hiroshi Mukae Citation: FEMS Yeast Research, 16(5), fow054; 2016 Nagasaki University (長崎大学), 博士(医学) (2017-09-06) doctoral thesis